2019
DOI: 10.3390/md18010030
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Identification of Putative Antimicrobial Peptides from Multi-Omics Data of the Lined Seahorse (Hippocampus erectus)

Abstract: Lined seahorse (Hippocampus erectus), the most widely cultivated seahorse in China, has been in short supply because of its important medicinal value; meanwhile, unnatural deaths caused by various diseases (especially enteritis) have limited their practical large-scale aquaculture. Antimicrobial peptides (AMPs), as the best alternative to antibiotics, have been extensively applied in agricultural practices. In this study, we identified 290 putative AMP sequences from our previously published genome and transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…The E3 ubiquitin ligases Atrogin-1 and MuRF1 are two key players to promote the degradation of proteins and contribute to skeletal muscle dysfunction. In aminal models, metabolic abnormalities induced by saturated fatty acid were accompanied by muscle dysfunction in mice 5 , 8 , 29 . Our present study revealed that high palmitic acid or a high caloric diet rich in palmitic acid promoted muscle dysfunction characterized by a reduction in muscle mass and muscle fiber size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E3 ubiquitin ligases Atrogin-1 and MuRF1 are two key players to promote the degradation of proteins and contribute to skeletal muscle dysfunction. In aminal models, metabolic abnormalities induced by saturated fatty acid were accompanied by muscle dysfunction in mice 5 , 8 , 29 . Our present study revealed that high palmitic acid or a high caloric diet rich in palmitic acid promoted muscle dysfunction characterized by a reduction in muscle mass and muscle fiber size.…”
Section: Discussionmentioning
confidence: 99%
“…In obesity, mitochondrial dysfunction and damage due to excessive fatty acid infiltration and accumulation in skeletal muscle may contribute to muscle atrophy 4 6 . Mitochondrial dysfunction triggers catabolic signaling pathways to induce and/or exacerbate muscle atrophy 7 , 8 . Mitochondrial integrity relies on the efficiency of mitochondrial quality control (MQC) processes, and their morphology is regulated by continuous fusion, fission, and mitophagy 9 13 .…”
Section: Introductionmentioning
confidence: 99%
“…AMPs usually have specific gene structures or come from the hydrolysis of some immune-related proteins, like histone, hemoglobin, thrombin, etc. [24]. In recent years, many AMPs have been identified by us through genome and transcriptome screening in fishes, such as amphibious mudskippers [25], line seahorse [24] and giant grouper [26].…”
Section: Introductionmentioning
confidence: 99%
“…[24]. In recent years, many AMPs have been identified by us through genome and transcriptome screening in fishes, such as amphibious mudskippers [25], line seahorse [24] and giant grouper [26]. Interestingly, our previous antibacterial experiments using AMPs/AMP precursors from mudskippers have revealed their efficiencies in inhibiting the growth of Micrococcus luteus [25], which suggested that AMPs might play some roles in KWM against infectious pathogens such as Ich.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, differential expression between male and female individuals was also analyzed for potential sexual variances and specificity. The data provides an overview of AMPs in the popular lined seahorse, which is a solid foundation for further investigation on development of AMP-based fish food and human drugs [7].…”
mentioning
confidence: 99%